Tibial plateau fractures – review of current concepts in management. Issue 2 (April 2017) - Jeelani, Ana; Arastu, Mateen H.
Abstract: Tibial plateau fractures represent a wide spectrum of injury patterns and encompass degrees of severity that are challenging to treat by even experienced orthopaedic trauma surgeons. The principles of treatment include respect for the soft tissues, restoring the congruity of the articular surface and reduction of the anatomic alignment of the lower limb to enable early movement of the knee joint. There are various surgical fixation methods that can achieve these principles of treatment. Recognition of the particular fracture pattern is important, as this guides the surgical approach required in order to adequately stabilize the fracture.